Co-pyrolysis of sugarcane bagasse and oil palm empty fruit bunch (EFB) / Hasnilshazuren Abu Hassan - Abu Hassan, Hasnilshazuren (Faculty of Applied Sciences, 2009)
Pyrolysis is an advanced and a technology to converts solid resources into liquid products which could be processed into liquid fuel and a value added chemicals. It converts at high yields of liquid products that can be stored and transported. The effect of process parameters such as pyrolysis temperature, heating rate on the yields of pyrolysis products and their gas flow rate utilized. This research only study about the effect of pyrolysis reactor temperature in the production of pyrolytic oil and char sample. The temperature of the pyrolysis reactor playing an important role in distribution of product yield. The pyrolytic products were analyzed by GCMS. This sugarcane bagasse sample was used to characterize the raw and char sample produced by using proximate and ultimate analysis. During pyrolysis, biomass thermally decomposed to solid charcoal, liquid oil, and hydrogen rich gases under an oxygen absence condition. Generally, hydrogen gas products are favored at high temperature. The percentage of product yield was different in different temperature of pyrolysis analysis. The higher the temperature, the higher pyrolytic oil produced.